An Evaluation Model for Authors' Academic Influence Based on Multi-source Heterogeneous Database in Bilingual Environment. (June 2020) - Deng, Zhijian; Zhang, Zhenhua; Xiong, Chun; Chen, Mingqin; Huang, Yanting; Li, Junran; Shen, Jiawen
Abstract: As the internationalization of academic rise up, it is insufficient to evaluate a scholar's influence only taking domestic academic contribution as reference. To have a better understanding of scholars' academic contribution in an international scale, this paper proposes a new evaluation system of academic influence based on the optimal dataset of entity recognition in bilingual environment. The new evaluation system has been experimented on a real literature dataset of DBLP. The research is conducted by the following steps. First, handle bilingual data. Second, optimize the literature data with entity recognition technology. Third, make an academic influence evaluation. Experiment results show that the new evaluation system is feasible and reasonable.